The use and functions of discourse markers in efl classroom interaction (2009)
The aim of this paper is to investigate classroom interaction in the context of English as a foreign language being the teacher a non-native speaker of the language. One specific aspect of classroom interaction and language use is the focus of attention, namely discourse markers (DMs). Using data from an EFL class, this study describes the occurrences and frequencies of DMs. It also provides an account for the main functions of DMs as they were used by a non-native teacher of English and five adult students of EFL. A qualitative analysis reveals that discourse markers fulfill a number of textual and interpersonal functions which may contribute greatly to the coherent and pragmatic flow of the discourse generated in classroom interaction. Key words: EFL classroom interaction, discourse analysis, discourse markers, non-native teacher, adult EFL students El artículo que aquí se presenta intenta investigar la interacción que ocurre en el aula de inglés como lengua extranjera cuando el profesor de inglés es no-nativo. Un aspecto específico de la interacción en el aula y del uso del lenguaje es la presencia de los marcadores del discurso (MD). Con base en datos empíricos, este estudio pretende describir las ocurrencias, la frecuencia y las funciones principales de los MD. El análisis cualitativo de los datos revela que los MD cumplen funciones tanto textuales como interpersonales que pueden facilitar y contribuir al flujo coherente y pragmático del discurso generado en la interacción de aula. Palabras clave: Interacción en el aula, análisis del discurso, marcadores del discurso, profesor de inglés no nativo, estudiantes adultos de inglés como lengua extranjera